Nghĩa của động từ “see” trong tiếng Anh nhìn từ góc độ ngôn ngữ học tri nhận /Hoàng Thị Hòa - Hoàng, Thị Hòa
The verb “see” is a verb of perception with the largest number of meanings (34 of both derivative and original). This has caused so many problems for users, especially for those who are non-native speakers. The author analyses all the meanings of the perceptional verb “see” and manages to explain its path of development from the cognitive linguistics’ point of view.